Analisis Materi Listrik dalam Pembelajaran IPA di Sekolah Dasar - Rahmawati, Aa; Nurlaili, Inayati; Pratama, Gibran Andika; Kurniawati, Wahyu (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Electricity is a physical phenomenon involving the flow of electrons that occurs due to differences in potential or voltage. Electricity plays a very important role in everyday life, such as for lighting, to power electronic devices and others. To understand electricity at the elementary school level, you have to start learning about electricity because it is important in learning science. Students learn about electricity sources, types of electrical devices, and simple concepts about current and voltage. The aim of this research is to provide a basic understanding of electricity, teach safety principles in the use of simple electrical tools. The method used in this research is the library study method. The technique used in collecting this data is the Listen and Note technique. The results of this research explain material regarding electricity. This material aims to provide students with basic knowledge of electricity that helps them understand the role of electricity in everyday life and develop simple problem solving skills related to electricity. This research is also useful for every reader to increase their knowledge of the world of science about electricity..